2020
DOI: 10.1177/2325967120s00411
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pectoralis Major Tendon Tears: A Systematic Review and Meta-Analysis of Operative and Nonoperative Treatment

Abstract: Objectives: The incidence of pectoralis major tendon tears is rising, and repair is generally considered, but there is a paucity of comparative data to demonstrate the superiority of operative treatment. We sought to compare the outcomes of operative and nonoperative treatment of pectoralis major tendon tears. We hypothesized that repair would result in superior outcomes compared to nonoperative treatment. Methods: In accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…There has been an increasing incidence of reported pectoralis major tears (PMT) in the last 20 years, likely due to an increased interest in weight training and athletics. 2 A 40% increase in incidence of this type of injury among NFL players in the last 22 years has been reported. 3 The typical mechanism involved in rupture of the pectoralis major is extension and external rotation of the muscle along with maximal contraction of muscle.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…There has been an increasing incidence of reported pectoralis major tears (PMT) in the last 20 years, likely due to an increased interest in weight training and athletics. 2 A 40% increase in incidence of this type of injury among NFL players in the last 22 years has been reported. 3 The typical mechanism involved in rupture of the pectoralis major is extension and external rotation of the muscle along with maximal contraction of muscle.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of PMT depends on the extent of the injury and physical demands of the patient. 2 Conservative line of management is indicated for contusions, partial tears, muscle intramuscular tears, and complete tears in low-demand patients. 2 Although the PM is not required for most activities in daily living, surgical management is indicated in the young and athletic patients to avoid loss of strength of muscle during adduction, forward flexion and internal rotation of the joint.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Functional outcomes and return to military duty rates after this surgery are excellent and in line with findings of large nonmilitary outcomes studies. 4,31 Nute et al 20 reported a 94% return to full duty rate and 5.4% reoperation rate in a large study of 257 military patients, while Balazs et al 3 reported a 95.3% return to full duty rate in a study of 214 military patients. We observed a similar trend in this study, with all 13 patients returning to full duty at a mean of 6 months after injury and only 1 patient indicating he was not satisfied.…”
Section: Discussionmentioning
confidence: 99%